What objects mean an introduction to material culture - Berger, Arthur Asa 1933-
"Arthur Asa Berger, author of an array of texts in communication, popular culture, and social theory, is back with the second edition of his popular, user-friendly guide for students who want to understand the social meanings of objects. In this broadly interdisciplinary text, Berger takes the reader through half a dozen theoretical models that are commonly used to analyze objects. He then describes and analyzes eleven objects, many of them new to this edition-including smartphones, Facebook, hair dye, and the American flag-showing how they demonstrate concepts like globalization, identity, and nationalism. The book includes a series of exercises that allow students to analyse objects in their own environment. Brief and inexpensive, this introductory guide will be used in courses ranging from anthropology to art history, pop culture to psychology"--Provided by publisher.